(untitled) (Indian Journal of Chemistry (IJC), 2024)
Presenting here an efficient and a simple protocol using 10 mol % of NiCl2.6H2O, 20 mol % of 2, 3-dihydroxy naphthalene, 50 mol % of CTAB, and 2 equiv. of NaOH in 2.5 mL of DMF at 150 °C for C-C bond forming Mizoroki-Heck coupling. Use of styrene and 4-methyl styrene with various aryl iodides and bromides having functionalities such as methyl, methoxy, nitro, fluoro, chloro, hydroxyl, trifluoromethyl, Methyl, and methoxy aryl halide showed smooth conversion with 50 to 93 % isolated yield. The electron-withdrawing groups like nitro at para-position gave a lower yield. The aryl iodides were found to be more reactive than aryl bromides. The advantages of this protocol are moderate to excellent yield in the absence of an inert atmosphere, and the use of cheap and readily available catalyst.